Effect of slag and limestone on the availability of phosphorus of an Oxisol planted with sugarcane - Prado, Renato de Mello; Fernandes, Francisco Maximino (Pesquisa Agropecuaria Brasileira, 2001)
The aim of this work was to evaluate the effect of slag and limestone, on the available P concentration of the soil planted with sugarcane. A field experiment was conducted in Ituverava, SP, Brazil, in a Red-Yellow Oxisol. Calcitic limestone and the slag were added in order to increase the base saturation to 50%, 75% and 100%, in addition to the control without correction. The linear effect of the slag on the soil available P, contrasting the lack of relationship when the limestone was applied, suggests that the positive effect of the slag is mainly due to the silicate effect than to the pH effect.